Desempenho reprodutivo de tilápia-do-Nilo (Oreochromis niloticus) em tecnologia de bioflocos (BFT) - ADRYADINE ALMEIDA DA COSTA (2025)
Nile tilapia (Oreochromis niloticus) is one of the most cultivated species in aquaculture due to its high productivity and resistance. Biofloc technology (BFT) is a sustainable solution to the challenges of production intensification, reducing water use and improving environmental conditions. The objective of this study was to evaluate the influence of BFT on: successive spawning of females (Experiment 1) and seminal quality of males subjected to different concentrations of settleable solids in successive collections. In Experiment 1, 30 Nile tilapia broodstock were allocated to five BFT experimental units (1 m³), with four females and two males per tank. The system was stabilized before the experiment, with controlled water temperature (28.59 ± 0.22ºC), settleable solids concentration below 50 mL/L and alkalinity above 100 mg/L. During the 5 weeks of study, 50% of the females spawned, and 35% of these spawned a second time during the same period. There were no significant differences between the first and second spawnings in characteristics such as volume and number of eggs, absolute and relative fecundity, and hatching rate, except for the smaller egg diameter, which was larger in the first spawning (P